KEBIJAKAN POLITIK PENDIDIKAN ISLAM ZAMAN SEKUTU - Lely Wahyu Ningrat; Faridi (STKIP Subang, 2026)
This article examines the dynamics of Islamic education in Indonesia during the arrival of the Allied Forces and the Netherlands Indies Civil Administration (NICA) in the period 1945-1949, a crucial phase in the early years of independence. The post-Proclamation political situation, marked by conflicts between the Republic of Indonesia, the Allied Forces, and the Dutch, had significant implications for the organization and development of Islamic education. Madrasahs, pesantren, and other Islamic educational institutions faced various challenges, ranging from strict supervision and limited institutional activities to threats of dissolution, as they were perceived as potentially supporting the national struggle. This study employs a qualitative approach using the historical method through library research on relevant primary and secondary sources. The findings indicate that the establishment of the Ministry of Religious Affairs in 1946 constituted an important milestone in the formal recognition of Islamic education as an integral part of the national education system. Furthermore, pesantren, madrasahs, and Islamic organizations such as Nahdlatul Ulama, Muhammadiyah, Persis, and Perti played strategic roles in sustaining and strengthening Islamic education amid political pressure and military conditions. The period of 1945-1949 not only represented a phase of survival for Islamic education but also laid the foundational basis for institutional structures, curriculum development, and the consolidation of Islamic educational identity oriented toward religious values, nationalism, and national character building.